PENGARUH KUALITAS SUMBER DAYA MANUSIA TERHADAP PERKEMBANGAN USAHA PADA KPRI PERTAGUMA KOTA MADIUN - Inggar Ariani Karendra (Universitas PGRI Madiun, 2016)
This study aims (1) to determine the quality of human resources at KPRI “Pertaguma” Madiun City, (2) To determine the development of business in KPRI “Pertaguma”, and (3) To determine the effect of the quality of human resources to the business development on KPRI “Pertaguma” Madiun City. The independent variable in this study is the quality of human resources while the dependent variable is business development. Sampling technique using a purposive sampling. The researcher uses purposive sampling technique as sampling technique. Results showed that there is difference between the effect of the quality of human resources to the business development on KPRI Pertaguma Madiun. Free variable at this research is the quality of human resource while variable tied is business development. It can be seen from the calculation of simple linear regression of Y = 61.738 + 0.210 X. Where the variable quality of human resources totaled0.210 shows the influence of the quality of human resources to the business development are positively correlated, meaning that any increase in the quality of human resources 1% resulted in higher business development at 0.210 units. Based on the results of the analysis can be said to be a significant relationship between quality of human resources and the business development, meaning that there is difference business development of the quality of human resources to the business development on KPRI Pertaguma Madiun.